Calculation of The Chain Ladder and Bornhoutter-Ferguson Methods in Calculating Claim Reserves for Insurance of Property Company in Sumatra - Julianty, Dila Tirta; Yulita, Tiara; Aprilia, Inaya Sathrani (Journal of Science and Applicative Technology, 2025)
Property insurance provides financial protection against the risk of loss due to damage or loss of insured property, such as buildings, vehicles, and equipment. Property insurance companies are required to maintain sufficient reserves to meet future claim obligations. Therefore, these companies need to accurately estimate claim reserves. This study aims to compare two methods of estimating property insurance claim reserves Chain Ladder method and Bornhuetter-Ferguson method. The data used in this research is secondary data obtained from property insurance in Sumatra, covering production and claims data from 2018 to 2023. The Chain Ladder method is a straightforward approach that uses historical claims development patterns to project future claims. The Bornhuetter-Ferguson method combines information from paid claims and estimates of the loss ratio from earned premium to predict reserves. Both methods are compared to assess their accuracy in estimating claim reserves using the Mean Absolute Percentage Error (MAPE). The results of this study indicate that the Bornhuetter-Ferguson method provides better estimates of claim reserves compared to the Chain Ladder method.